Respuestas

2013-08-30T01:18:20+02:00
. 4x² - 7x - 2 = 0

2. 9x² - 81x + 50 = (3x - 25) (3x - 2)

3. 18x² - 17x -187 = (6x + 17) (3x - 11)

4. - 4x² + 4x + 3 = (x – ³/₂)(x + ½) 

5. 6x² - x – 2 = (3x - 2) (2x + 1)

6. 6x² - 2x – 4 = (x - 1) (x + ⅔) 

7. 3x² + 8x – 35 = (3x - 7) (x + 5) 

8. 9a² + 9ab - 18b² = (a + 2b) (a - b)

9. 4x² +17x -15 = (4x - 3) (x + 5)

10. 15x² + x - 2 = (5x + 2) (3x - 1)

11. 7x² + 13x – 2 = (x + 2)(7x - 1) 

12. 6x² + 17x + 10 = (x + 2) (6x + 5)

13. 2x² - x - 1 = (x - 1) (2x + 1)

14. 4x² + 7x + 3 = (x + 1) (4x + 3)

15. 3a² + 10ab + 7b² = (3a + 7b) (a + b)

16. 10n² - n – 2 = (2n - 1) (5n + 1)

17. 6a² + 5am - 4m² = (3a + 4m) (2a - m)

18. 6x² + 15x + 6 = 3 (x + 2) (2x +1)

19. 6x² - x – 2 = (2x + 1) (3x - 2)

20. 2x² + 3x + 1 = (x + 1) (2x + 1)

21. 2x² + 4x - 48 (x + 6) (x - 4)

22. 5x² - 40x + 80= (x - 4) (x - 4)

23. 4x² + 44x + 72 = (x + 9) (x + 2)

24. 3x² + 21x - 24 = (x + 8) (x - 1)

25. 25x² + 30x + 9 = (5x + 3) (5x + 3) 

26. 4x² - 4x + 1 = (2x - 1) (2x - 1) 

27. 2x² + 12 x + 18 = (x + 3) (x + 3)

28. 15x² - 29x - 14 = (x + 8) (x - 20)

29. 10x² - 13x – 3 = (5x + 1)(2x - 3)

30. 10x² + 16x - 8 = (5x - 2) (x + 2)

31. 16x² + 8x + 1 = (4x + 1) (4x + 1)

32. 5x² - 10x - 15 = (x - 3) (x + 1)

33. 2x² +11x + 9 = (x + 1) (2x + 9)

34. 6x² - x - 2 = (2x + 1)(3x - 2)